Literature Review on the Solar Energy Potential for Botswana - Mutoko, Wilbert R.; Mutoko, Phillis (European Scientific Journal, ESJ, 2019)
Renewable energy sources are easily accessible and clean to the environment. Solar energy is one of the best forms of renewable energy, particularly for a country such as Botswana. Paradoxically, Botswana finds herself importing electricity and experiencing power cuts, yet she has abundant sunshine almost all-year round that could be converted to electric power. This paper seeks to investigate through literature search, the potential for Botswana to convert her copious solar radiation into solar energy. A comparison of different forms of renewable energy are made. Particular attention is drawn to the case of Australia which has experience in use of solar energy and has a similar climate to that of Botswana. Findings from literature search reveal that Botswana stands a great chance of using solar power to improve the livelihood of its people and businesses. Recommendations to policy makers and the private sector are that there is urgent need to put in place policies, regulations and frameworks to support solar generation and reduce reliance on electricity importation and coal production which is not sustainable. The authors propose a conceptual model to help policy makers in implementing solar energy projects in Botswana.